A project paper on Bank of the Philippine Islands - Alagar, Rowena E. (Animo Repository, 1999)
The banking industry is one of the most essential industries in any country. The organization and performance of the banking system dictates the flow of money in circulation as well as the interest rates in which most individuals and business rely on. Furthermore, a strong banking system leads and translates to an economy that can cushion crises and difficulties. This type of business demands the most public trust and responsibility because it involves acceptance and custody of depositors funds. Hence, the banking business is property subject to strict regulations to safeguard the public interest. The Philippine Commercial Banking Industry consists of 52 players with assets ranging from P 270B to P2.1B. Now that Asia experiences a currency crisis. The Bangko Sentral ng Pilipinas has formulated stricter rules which include minimum capitalization requirement. The said rule is currently being resented by a number of smaller banks but despite this The Bangko Sentral is tough on its decision in its desire to make the industry stronger. Bank of the Philippine Islands, a part of the Ayala Group of Companies, is one of the major players in the industry. It is considered as the industry in terms of electronic banking, expanded branch network, products and services, and stability. It has always been awarded as the Most Financial Sound Institution in Asia by known international organizations such as Far Eastern Economic Review and Standard & Poors. In fact, it has maintained its leadership and stability despite the Asian currency turmoil. This paper discusses how can a leader maintain its leadership and dominance in the market. Hamel & Prahalads Core Competencies framework inspire the proposed strategies for the Bank. Some concepts from Thomas J. Peters and Robert H. Waterman, Jrs Competing for the Future were also used in the strategy formulation.